2019
DOI: 10.3390/cancers11122039
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Multi-Organ Metastases from Chemo-Resistant Triple-Negative Breast Cancer Are Prevented by Interfering with WNT-Signaling

Abstract: Triple-negative breast cancers (TNBCs), which lack specific targeted therapy options, evolve into highly chemo-resistant tumors that metastasize to multiple organs simultaneously. We have previously shown that TNBCs maintain an activated WNT10B-driven network that drives metastasis. Pharmacologic inhibition by ICG-001 decreases β-catenin-mediated proliferation of multiple TNBC cell lines and TNBC patient-derived xenograft (PDX)-derived cell lines. In vitro, ICG-001 was effective in combination with the convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…3f). It has been shown that the Wnt/β-catenin network correlates with high metastatic TNBC behavior 39,40 . Therefore, metastases generated from primary tumors were evaluated.…”
Section: Anti-il-3r-evs Impair Tumor Angiogenesis and The Formation Omentioning
confidence: 99%
“…3f). It has been shown that the Wnt/β-catenin network correlates with high metastatic TNBC behavior 39,40 . Therefore, metastases generated from primary tumors were evaluated.…”
Section: Anti-il-3r-evs Impair Tumor Angiogenesis and The Formation Omentioning
confidence: 99%
“… 35 ICG-001, an inhibitor of β-catenin diminished the proliferation of MDA-MB-231 cells by synergizing with cisplatin and doxorubicin. 36 β-catenin, the essential factor of the canonical Wnt signaling, was increased in Tam-resistant BC cell lines, while the inhibition of β-catenin by XAV939 partially reversed Tam resistance by its impact on the cell cycle by lowering the expression of β-catenin and β-catenin-modulated downstream targets such as CCND1. 37 Moreover, CCND1 has been proposed to accelerate binding between β-catenin and Nanog in the nucleus, thus facilitating cervical carcinoma cell colony formation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been published in the last decade that correlate changes in Wnt ligands, receptors, gatekeepers, and downstream effector molecules to almost every type of human tumor. Dysregulation of both canonical and noncanonical Wnt signaling has been shown in numerous cancers [ 16 , 22 , 37 , 54 , 58 , 59 , 60 , 61 , 62 , 63 ]. Table 1 lists reports of Wnt pathway alterations in numerous tumor types.…”
Section: Aberrations In Wnt Signaling In Cancermentioning
confidence: 99%